Lowlands Ware 1 containers from Xanten/Colonia Ulpia Traiana - Liesen, Bernd (Rei Cretariae Romanae Fautorum Acta, 2017)
The aim of this paper is to discuss the Arentsburg 140–142 vessels from Xanten/Colonia Ulpia Traiana (Germany). It also provides some additional information on the chemical composition and the distribution of Lowlands Ware 1. This pottery group is frequently found in the northern part of Germania inferior. Dutch and Belgian scholars have studied it for a long time, but the finds in the German part of the province are barely examined. According to De Clercq and Degryse the pottery was produced in the region of Bergen op Zoom (the Netherlands), although we do not know any production sites yet. Arentsburg 140–1422, a bowl with thickened rim, outnumbers all other types by far. As these vessels were distributed over far distances and never exposed to fire one can assume that they were used for transport. The content is unknown.